Mesoporous adsorbent for CO2 capture application under mild condition: A review. Issue 2 (April 2019) - Azmi, A.A.; Aziz, M.A.A.
Graphical abstract: Highlights: Recent trends in mesoporous adsorbents for CO2 capture under mild condition. Mesoporous adsorbents with amine functionalization were discussed in detail. Biomass based absorbents were discussed due to their resource availability. Future opportunities of CO2 capture on mesoporous materials were presented. Abstract: Carbon dioxide (CO2 ) capture and storage have been suggested as an effective strategy to reduce global greenhouse gas emissions. In recent years, many studies were carried out to develop highly efficient materials, such as zeolites, porous carbons, metal-organic frameworks (MOFs) and metal oxides for capturing CO2 . In addition, interest in studying amine species grafting with mesoporous materials to improve CO2 capture by amino groups have increased tremendously. These modified materials provide excellent CO2 uptake capacity, fast adsorption kinetics and easy regeneration with stable cycling performance. Not to mention, the utilisation of adsorbents derived from biomass sources for CO2 capture under low adsorption temperature and ambient pressure was recently reported by many researchers. Such adsorbents are desirable for its high surface area, less energy consumption, less expenses during regeneration and highly available. Herein, mesoporous materials are thoroughly described for CO2 capture under mild condition (ambient temperature and pressure). In addition, a recommendation of characteristics and properties for effective porous adsorbent, functionalisation of amine groups, and utilisation of biomass-based adsorbent were reviewed in this work. A concise conclusion and future outlook was also proposed.